Swedish Abdominal Massage Sebagaia Terapi Komplementer Untuk Menjaga Pola Eliminasi Defekasi di ICU RSUD Sukoharjo : Swedish Abdominal Massage Sebagaia Terapi Komplementer Untuk Menjaga Pola Eliminasi Defekasi di ICU RSUD Sukoharjo - Cika Novitasari; Fida’ Husain; Yohana Ika P; Endar Sulistyo (Jurnal Keperawatan Duta Medika, 2023)
Introduction: Constipation in critical patients is defined as no defecation for at least 3-4 days of care in the ICU, this is due to decreased gastrointestinal motility. There are two management of constipation, namely pharmacological and non-pharmacological. Pharmacological treatment can be done by using laxatives. As for non-pharmacological, it can be done by increasing the consumption of fiber intake and adequate fluid intake. Apart from food intake, one of the actions that can help prevent and treat constipation is by massaging the stomach area, precisely in the colon area, which is called abdominal massage. Objectives: : to determine whether there is an effect of Swedish abdominal massage on the regularity of defecation elimination patterns. This research design uses a descriptive research design with a case study with a form of observation where the researcher will reveal the influence between the variables and 2 respondents. Methods: this type of research is descriptive with a case study. The application was carried out on 2 patients selected by purposive sampling method with inclusion and exclusion criteria. This Swedish abdominal massage action is carried out for 15 minutes once a day for 3 days. The research instrument used Swedish abdominal massage SOP, observation sheets and informed consent. This research has gone through an ethical test with number 081/V/AUEC/2023. Results: from the results of observations made for 3 days on 2 respondents Mr. G and Mr. S indicates that respondents can defecate starting on days 2 and 3, which means that there is an improvement in the pattern of defecation elimination in 2 respondents. Conclusions: from this study Swedish abdominal massage is a simple massage therapy that can help maintain regular defecation elimination patterns. Keyword: Swedish Abdominal Massage, Defecation Elimination Pattern,Intensive Care Unit.